Effects of pulsed electric field-assisted thawing on the characteristics and quality of Pekin duck meat. (1st October 2022) - Lung, Chun-Ta; Chang, Chao-Kai; Cheng, Fang-Chi; Hou, Chih-Yao; Chen, Min-Hung; Santoso, Shella Permatasari; Yudhistira, Bara; Hsieh, Chang-Wei
Graphical abstract: Highlights: Pulsed electric field reduce duck meat thawing loss and shorten 50% thawing process. The quality and texture of duck meat were maintained by pulsed electric field thawing. Pulsed electric field protect meat structural integrity and reduce 70% ice crystals damage. Pulsed electric field could improve the stability of water molecules migration during thawing process. Abstract: We determined the effect of pulsed electric field (PEF)-assisted thawing on the texture and muscle tissue of Pekin duck meat. The results indicated that 1–4 kV/cm of PEF shortened the thawing time by 20%–50%. Furthermore, 1–3 kV/cm of PEF-assisted thawing reduced the effect of thawing on meat quality, decreased thawing loss by 28% and protein loss by 19%, and maintained meat quality similar to that of fresh meat. Using low-field nuclear magnetic resonance, we confirmed that PEF stabilized the water retention capacity of muscle tissues during thawing. Microstructure and secondary structure analyses revealed that PEF accelerated the melting of ice crystals, reducing the damage caused by ice crystals by 70% and maintaining the stability of the α-helix and β-sheet. These results revealed the potential of PEF-assisted methods for use in thawing meat.